The importance of professional based questionnaire in the dog’s acute and chronic pain evaluation - MARKOVSZKY, AK; DANES, M; DUMITRESCU, E; MUSELIN, F; STANCU, AC; BECSKEI, Z; PUVAČA, N; CRISTINA, RT (Journal of the Hellenic Veterinary Medical Society, 2021)
The measurement of pain levels is made differently depending if acute or chronic pain is diagnosed, objective (e.g. cortisol, prolactin, serotonin, catecholamines, or the cardiac frequency and arterial pressure evaluation) or subjective methods being imagined. All subjective methods are including questionnaires and specific additional methods. The aim was the verifying the effectiveness of drug and physiotherapy combinations by using an owner based questionnaire for the chronic patients and a veterinary professional based questionnaire for the acute pain patient group. In this study a total of 20 dogs with observable pain were selected and two groups (n = 10 / group), constituted: G1 - chronic pain, and G2 - acute pain. The treatment of dogs with acute signs of pain was made oral or injectable with NSAIDs administration and for dogs with signs of chronic pain, physiotherapy treatment and drug therapy was administered. The owners of the dogs with chronic pain received the HCPI questionnaire in order to evaluate their dog’s pain level subjectively. For the dogs with acute pain the veterinarian filled out the short form of Glasgow Composite Measure Pain Scale (CMPS-SF). After initiating a Paired t-test in Excel 2010 with the scores obtained with HCPI and CMPS-SF, there was observed a significant reduction of pain after associated drug administration and physiotherapy and no significant evidence of acute pain after drug therapy. The used physiotherapy and drug combinations delivered a significant reduction of chronic pain, both clinically and visually mirrored in score reduction after treatments. The HCPI questionnaire could be considered a valuable tool for evaluating chronic pain in patients in the clinic environment. The CMPS-SF has also proven to be a very useful questionnaire in diagnose of acute pain and evaluation of the effectiveness of drug therapy used.